International Practice Theory - Bueger, Christian (Springer International Publishing, 2018)
International Practice Theory is the definitive introduction to the practice turn in world politics, providing an accessible, up-to-date guide to the approaches, concepts, methodologies and methods of the subject. Situating the study of practices in contemporary theory and reviewing approaches ranging from Bourdieu's praxeology and communities of practice to actor-network theory and pragmatic sociology, it documents how they can be used to study international practices empirically. The book features a discussion of how scholars can navigate ontological challenges such as order and change, micro and macro, bodies and objects, and power and critique. Interpreting practice theory as a methodological orientation, it also provides an essential guide for the design, execution and drafting of a praxiographic study. Christian Bueger is Professor of International Relations at Cardiff University, UK, Honorary Professor at the University of Seychelles, and a Research Fellow at the University of Stellenbosch. Frank Gadinger is Senior Researcher and Head of a Research Unit at the Centre for Global Cooperation Research, University of Duisburg-Essen, Germany. .